Analisis Kepatuhan dan Kinerja Pengendalian Internal dalam Mengurangi Tingkat Fraud pada Perusahaan - Selsabila Nur Aprillia; Zainal Muttaqin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The effort to achieve financial accountability and transparency in an organization, various challenges arise, including actions that can lead to fraud. Fraud is a serious threat threats that can cause financial and reputational losses to a company. The purpose of this research is to analyze compliance and the performance of internal controls in reducing the level of fraud in a company. The research method used in this study is qualitative research. The type of research employed is literature study. The research findings indicate that high compliance with internal controls can create a work environment that values transparency, accountability, and integrity, where employees feel safe to report fraud occurrences and support efforts to prevent and take appropriate actions, thus significantly reducing the level of fraud. The performance of internal controls can be measured through the effectiveness of implementing control policies and procedures.